Hereditary Nobility in Local Governance System of Kazan Province in Second Half of 19th Century - E. V. Mironova (Научный диалог, 2025)
This study examines the role of the nobility within the local governance system of Kazan Province during the late 19th century, an important aspect of pre-revolutionary Russian statehood. A historiographical review reveals a sustained scholarly interest in the history of noble civil service, particularly at the regional level. However, there is a notable absence of specialized works focusing on the history of Kazan’s nobility within provincial and district governmental institutions, which underscores the academic significance of this article. The chronological scope of the research spans from 1861, when new administrative bodies were established to implement reforms in the early 1860s, to the adoption of the new “Provincial Statute” (1890) and “Municipal Statute” (1892). The author illustrates the formation of a bureaucratic apparatus composed of hereditary nobles from Kazan Province in the context of changing government policies during the reigns of two emperors — Alexander II and subsequently Alexander III. Based on an analysis of materials from memorial books, address calendars, and official lists of civil servants, it is concluded that hereditary nobles held key positions within the local bureaucratic apparatus of civil and judicial authorities and predominated in district administration.